2007
DOI: 10.1089/ars.2007.1659
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 in Tumors: Is It a False Friend?

Abstract: Heme oxygenase-1 (HO-1) catalyzes the oxidation of heme to biologically active products: carbon monoxide (CO), biliverdin, and ferrous iron. It participates in maintaining cellular homeostasis and plays an important protective role in the tissues by reducing oxidative injury, attenuating the inflammatory response, inhibiting cell apoptosis, and regulating cell proliferation. HO-1 is also an important proangiogenic mediator. Most studies have focused on the role of HO-1 in cardiovascular diseases, in which its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
317
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(338 citation statements)
references
References 168 publications
(295 reference statements)
19
317
1
1
Order By: Relevance
“…HO-1 is an antiapoptotic gene product that is overexpressed in cancers (Jozkowicz et al, 2007), and expectedly, lack of HO-1 has been shown to lead to sensitization of cells to death (Fang et al, 2004;ChenRoetling et al, 2005;Jozkowicz et al, 2007). Consistently, cells lacking p53 and hence expressing reduced HO-1 are also more susceptible to death, and silencing HO-1 expression promotes cells death upon H 2 O 2 treatment only in p53-proficient cells (this report), indicating that HO-1 is indeed a target of p53 that is responsible for p53-dependent cellular survival, although probably not the only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 is an antiapoptotic gene product that is overexpressed in cancers (Jozkowicz et al, 2007), and expectedly, lack of HO-1 has been shown to lead to sensitization of cells to death (Fang et al, 2004;ChenRoetling et al, 2005;Jozkowicz et al, 2007). Consistently, cells lacking p53 and hence expressing reduced HO-1 are also more susceptible to death, and silencing HO-1 expression promotes cells death upon H 2 O 2 treatment only in p53-proficient cells (this report), indicating that HO-1 is indeed a target of p53 that is responsible for p53-dependent cellular survival, although probably not the only.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 with its antioxidant, antiapoptotic and proangiogenic properties has been shown to be overexpressed in cancers (Ferris et al, 1999;Petrache et al, 2000;Jozkowicz et al, 2007;Gozzelino et al, 2010). It regulates cellular homeostasis and protects against cellular and tissue injury, and consistently, HO-1-deficient mice were found to be significantly more susceptible to tissue injury than their wild-type counterparts (Chen-Roetling et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, possible roles in different pathophysiology patterns are emerging, such as protection of the endothelium from oxidative stress. 4,6,7 HO-1 may also be important in cardiovascular disease and in apoptosis, 5,9,19,20 and there is also evidence that HO-1 may be linked experimentally to angiogenesis via VEGF. [10][11][12]18,21 It is therefore notable that we report good correlations between HO-1 and VEGF (r40.52) (although we acknowledge the possibility of small number error) in the absence of cancer, but that this correlation in markedly weaker in the presence of cancer (r ¼ 0.12).…”
Section: Discussionmentioning
confidence: 99%
“…PDT induced p38 activation has by others also been associated with induction of VEGF using both BPD and Hypericin as photosensitizers (Hendrickx et al 2005, Solban et al 2006) and activation of p38 after hypericin PDT is in addition shown to upregulate cyclooxygenase-2 (Hendrickx et al 2003) and heme-oxygenase 1 (Kocanova et al 2007). Induction of both VEGF (Ferrara & Gerber 2001, Kowanetz & Ferrara 2006, COX-2 (Bakhle 2001) and heme-oxygenase (Jozkowicz et al 2007 Protein NuTu-19 WiDr A-431 p-EGFR decrease no effect no effect EGFR no effect no effect no effect p-ERK increase increase decrease ERK no effect no effect no effect p-JNK increase not detected not detected JNK no effect no effect no effect p-p38 increase increase increase P38 no effect no effect no effect Protein NuTu-19 A-431 p-EGFR decrease decrease EGFR decrease no effect p-ERK increase -ERK no effect -p-JNK --JNK no effect -p-p38 increase -P38 no effect - …”
Section: The Impact Of Mapk Signallingmentioning
confidence: 99%